IMPLEMENTASI METODE ECONOMIC ORDER QUANTITY (EOQ) PADA SEDIAAN KNOP JENDELA UD. IN JA, SAMARINDA - Gozali, Ade Setiawan (University of Surabaya, 2012)
Inventory is very great influence on the cost aspects of a company. If a company has a stock that is too large it will inflict a financial loss because it requires huge investment costs, but the lack of Inventory will also impact on service levels, so that could prejudice the company. The research was conducted at UD. In Ja, Samarinda. UD. In Ja is a distributor of various types and brands of property. This study focused only on the type of property ,window knop with two brands namely Dekkson And Klinsman. This study uses an Economic Order Quantity (EOQ) method approach with a deterministic model to determine the optimal pair amount. With this method it is known how many orders are fixed and when to perform re-ordering as well as the maximum pair. This study uses inventory data for six months from february to july 2011. Calculation of the total inventory cost before the EOQ, - and based on the results of planning inventory with EOQ method, the total inventory cost is reduced to 6,3% .With the application of EOQ method, UD. In Ja able to optimize the amount of inventory, the total cost and service levels.